Getting in People's Faces: On the Symbiotic Relationship between the Media and Police Gang Units. Issue 2 (1st February 2018) - Gravel, Jason; Wong, Jennifer S.; Simpson, Rylan
ABSTRACT: The current study explores the relationships among high-profile homicide incidents, media representations of gang homicides, and the establishment of specialized police task forces in British Columbia, Canada. The sample includes all articles on homicide published between 2004 and 2010 in a major daily newspaper ( N = 2, 873). We examine the attention given to gang-related homicides compared to other homicides, explore the impact of high-profile shootings on trends in reporting, and discuss the timing of media reports in relation to the creation of specialized police forces. Results are discussed with respect to the symbiotic relationship between police organizations and the media.